Analisis Kekerasan Hasil Pengelasan Gas Tungsten Arc Welding pada Baja ST 37 dengan Variasi Media Pendingin - Gede Agus Widiantara; I Nyoman Pasek Nugraha; Kadek Rihendra Dantes (Universitas Muhammadiyah Yogyakarta, 2021)
Cooling media is a substance that increases the hardness value of a material through a heat-treatment process. This study aims to determine the effect of cooling media on the hardness of ST 37 steel due to Gas Tungsten Arc Welding (GTAW). The independent variables, namely water cooling media, seawater cooling media, and oil cooling media, while the dependent variable is the hardness. The specimens using water cooling media, the hardness in the weld area is 47.19 kg/mm2, in the HAZ area the it is 54.6 kg/mm2, and the base metal gets a value of 40.87 kg/mm2. While the specimens with seawater cooling media get a value in the weld area of 76.37 kg/mm2, in the HAZ area it gets a value of 83.89 kg/mm2 and the base metal gets a value of 70.13 kg/mm2. The specimens with oil cooling media the value in the weld area is 40.77 kg/mm2, in the HAZ area it gets a value of 43.32 kg/mm2 and the base metal gets a value of 36.09 kg/mm2 . From the hardness values obtained, specimens immersed in seawater cooling media have the higher hardness values compared than water and oil cooling media.